Digital fantasy painting - Burns, Michael 1968- (New York Watson-Guptill Publications, 2002)
"Digital Fantasy Painting provides a complete overview of the art of fantasy painting. Featuring the work of some 35 renowned fantasy artists, the book begins with a review of the most popular software employed by fantasy artists, before continuing with deconstructed examples of specially created pieces that reveal insights into how the experts go about creating their art. Each example features step-by-step illustrations, helping to demystify the often complex and confusing processes involved. The book ends with a showcase of work that will surprise, delight, and inspire." -- Provided by publisher
FA-2887g donated by Isabel Caruncho.
Keywords: Computer graphics; Painting -- Digital techniques; Three-dimensional display systems; Computer art; Fantasy in art